ON THE QUESTION OF MODERNIZATION AND CREATION OF FORGING AND THERMAL EQUIPMENT OF THE NEW GENERATION - S. S. Tkachenko; V. V. Korobeynikov (Литьë и металлургия)
Three fundamental principles of modern production: Saving resources; Environmental cleanliness; Security. During the reconstruction, re-equipment, modernization and creation of a new thermal equipment, it is necessary to choose units and technologies that provide greater efficiency and higher efficiency equipment, strict compliance with environmental and safety standards.